Heterogeneous activation of persulfate by CuMgAl layered double oxide for catalytic degradation of sulfameter - Zhang, Hongmin; Jia, Qingzhu; Yan, Fangyou; Wang, Qiang (Green energy & environment, 2022)
In this study, a series of CuMgAl layered double oxides (CuMgAl-LDOs) were obtained via calcination of CuMgAl layered double hydroxides (CuMgAl-LDHs) synthesised via a co-precipitation method. The results show that CuMgAl-LDO can be prepared using an optimal Cu : Mg : Al molar ratio of 3 : 3 : 2, NaOH : Na2CO3 molar ratio of 2 : 1, and calcination temperature of 600 °C. CuMgAl-LDO is a characteristic of mesoporous material with a lamellar structure and large specific surface area. The removal efficiency of sulfameter (SMD) based on CuMgAl-LDO/persulfate (PS) can reach > 98% over a wide range of initial SMD concentrations (5–20 mg L−1). The best removal efficiency of 99.49% was achieved within 120 min using 10 mg L−1 SMD, 0.3 g L−1 CuMgAl-LDO, and 0.7 mmol L−1 PS. Kinetic analysis showed that the degradation of SMD was in accordance with a quasi-first-order kinetic model. The stability of the CuMgAl-LDO catalyst was verified by the high SMD removal efficiency (> 97% within 120 min) observed after five recycling tests and low copper ion leaching concentration (0.89 mg L−1), which is below drinking water quality standard of 1.3 mg L−1 permittable in the U.S. Radical scavenging experiments suggest that SO4·− is the primary active species participating in the CuMgAl-LDO/PS system. Moreover, our mechanistic investigations based on the radical scavenging tests and X-ray photoelectron spectroscopy (XPS) results indicate that Cu(II)–Cu(III)–Cu(II) circulation is responsible for activating PS in the degradation of SMD and the degradation pathway for SMD was deduced. Accordingly, the results presented in this work demonstrate that CuMgAl-LDO may be an efficient and stable catalyst for the activation of PS during the degradation of organic pollutants. CuMgAl-LDO/PS system exhibited an excellent catalytic performance for the degradation of SMD with low leaching of copper ion and high reusability, and activation of PS mechanism through electron transfer as Cu(II)–Cu(III)–Cu(II) was proposed. [Display omitted]